Effect of pressure on the quality of pesticide application in orchards - Di Prinzio, Alcides; Behmer, Sergio; Magdalena, Jorge Carlos; Chersicla, Germán (Instituto de Investigaciones Agropecuarias (INIA), Chile, 2023)
Only part of the active ingredient used in agrochemical applications in orchards is retained on the trees. The product that is not retained is lost as sedimentation in the soil and as drift, the latter being a major source of environmental pollution. Unfavorable atmospheric conditions affect the uniformity of distribution and increase product loss. This can be mitigated by the utilization of larger drops. The objective of the present work was to evaluate the effect of service pressure on distribution in the trees and product loss by using a conventional hydro pneumatic sprayer. A fluorescent tracer was applied on fruit trees by an airblast sprayer, with two treatments: high pressure (1800 kPa) and low pressure (500 kPa). Samples were collected from the trees, in columns and from the soil. The results indicated that there were no differences between the two treatments in the total quantity of deposits recovered from leaves. There was one third less drift with the low-pressure than with the high-pressure treatment, whereas deposits on the soil were similar with the two treatments, with the low-pressure treatment presenting a higher concentration of deposits in the proximity of the treated row. In conclusion, the use of sprayer systems that operate with low pressure is a valid alternative to reduce environmental pollution because it tends to loss to the area where the treatment is being applied, without affecting deposits on the trees.